Four new sympatric species of Tethya (Demospongiae: Hadromerida) from Abrolhos Archipelago (Bahia State, Brazil) - Ribeiro, Suzi M.; Muricy, Guilherme (Zootaxa, 2004)
Four new species of Tethya are described from coral reefs in Abrolhos Archipelago (Brazil). Tethya brasiliana sp. nov. is green or yellow externally, yellowish orange internally, and its micrasters are strongylasters, microspherasters and microoxyasters. Tethya cyanae sp. nov. is dark blue externally; its micrasters are tylasters, oxyasters and microoxyasters. Tethya ignis sp. nov. is orange externally and internally, and its micrasters are tylasters and completely microspined oxyasters. Tethya rubra sp. nov. is red or yellow externally, and it has tylasters and oxyasters with branched and twisted rays. Scanning electron microscopy of microscleres was essential for distinction of Brazilian species of Tethya. The diversity of Tethya from the Brazilian coast has increased from five to nine species. Abrolhos Archipelago harbors the greatest diversity of Tethya in the Atlantic, with four species, three of which are provisional endemics.